Improving virtual machine consolidation for heterogeneous cloud computing datacenters - Rodrigues, Joao Antonio Magri [UNESP]; De Oliveira, Fabiola Martins C.; Lobato, Renata Spolon [UNESP]; Spolon, Roberta [UNESP]; Manacero, Aleardo [UNESP]; Borin, Edson (Institute of Electrical and Electronics Engineers (IEEE), 2019)
Datacenters in cloud computing systems may consist of thousands of computing nodes and communication devices, requiring virtual machine placement to optimize resources utilization. Heterogeneous environments of current datacenters have not been properly evaluated yet when the number of processing nodes and network devices is considered. This paper presents an approach to place virtual machines to minimize both the number of employed computing nodes and communication costs in heterogeneous environments. We evaluate our results against other known algorithms to show the efficiency of the proposed approach, which outperforms a state-of-the-art algorithm with a result of up to 13% better for network improvement while achieves the same number of computing nodes.
Keywords: Cloud computing; Heterogeneous systems; Virtual machine placement